2011
DOI: 10.1148/radiol.11101175
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Transstenotic Pressure Gradients in Porcine Renal Artery Stenoses by Using Vastly Undersampled Phase-Contrast MR Angiography

Abstract: Purpose:To compare noninvasive transstenotic pressure gradient (TSPG) measurements derived from high -spatial-and temporal-resolution four-dimensional magnetic resonance (MR) fl ow measurements with invasive measurements obtained from endovascular pressure wires with digital subtraction angiographic guidance. Materials and Methods:After Animal Care and Use Committee approval, bilateral renal artery stenosis (RAS) was created surgically in 12 swine. Respiratory-gated phase-contrast vastly undersampled isotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 26 publications
(20 reference statements)
0
38
0
1
Order By: Relevance
“…Recently, multi-dimensional investigations of velocity and flow in restrictions associated with highvelocity jet streams have been reported in clinical data [32][33][34]. Volumetric 4D PC sequences also offer the possibility to track the position of a restriction over the cardiac cycle.…”
Section: An Alternative Non-invasive Methods For Blood Velocity Measurmentioning
confidence: 99%
“…Recently, multi-dimensional investigations of velocity and flow in restrictions associated with highvelocity jet streams have been reported in clinical data [32][33][34]. Volumetric 4D PC sequences also offer the possibility to track the position of a restriction over the cardiac cycle.…”
Section: An Alternative Non-invasive Methods For Blood Velocity Measurmentioning
confidence: 99%
“…A negative correlation has been identified between the concentration of omentin and the thickness of the intima-media complex in carotid arteries, their stiffness, BMI, waist circumference, systolic arterial pressure, fasting blood glucose level and the insulin resistance index HOMA-IR (homeostasis model assessment of insulin resistance). Consequently, omentin is closely linked to the metabolic syndrome and its deficiency plays a significant role in the development of atheromatosis in these patients [33][34][35]. Zhong et al have demonstrated lower plasma levels of omentin in patients with acute coronary syndrome (ACS) or stable angina pectoris than in the control group.…”
Section: Omentynamentioning
confidence: 99%
“…Stwierdzono negatywną korelację stężenia omentyny z grubością kompleksu intima-media tętnic szyjnych, ich sztywnością, BMI, obwodem talii, skurczowym ciśnieniem tętniczym, stężeniem glukozy na czczo oraz wskaź-nikiem insulinooporności HOMA-IR (homeostasis model assessment of insulin resistance). Dlatego też omentyna jest ściśle związana z ZM, a jej niedobór odgrywa znaczącą rolę w rozwoju miażdżycy u tych pacjentów [33][34][35]. Zhong i wsp.…”
Section: Omentynaunclassified
“…While the results from the turbulence intensity mapping agreed well with reference values from computational fluid dynamics data, the accuracy of the MRI-based wall shear stress estimates was found to be very sensitive to different parameters, especially to spatial resolution, and wall shear stress values over 5 N/m 2 were not well resolved.…”
mentioning
confidence: 52%